If p + q +r = 2, p2 + q? + r 2 = 30 and pqr = = = 10, then the value of (1 – p) (1 – 0)(1 – r) willbe Options: A. -18 B.-24 C. -27 D. -35 Plz tell the correct answer with correct option Fast!!! About the author Lyla

Answer: I think so this will be solution. Step-by-step explanation: Correct option is B qr=p 2 + a c As a(p+q) 2 +2bpq+c=0 and a(p+r) 2 +2bpr+c=0 Then q,r are roots of a(p+x) 2 +2bpx+c=0 ⇒ap 2 +ax 2 +2pax+2bpx+c=0 ⇒ax 2 +(2pa+2pb)x+c+ap 2 =0 Hence, product of roots is qr= a c+ap 2 ⇒qr=p 2 + a c Reply

p:q = r:s => p/q = r/s . Squaring both sides p^2/q^2 = r^2/s^2 => (p^2+q^2)/q^2 = (r^2+s^2)/s^2 => (p^2+q^2)/(r^2+s^2) = q^2/s^2 ……(1) p/q = r/s. Multiplying both sides with qs => pqs/q = rqs/s => pq(s/q)= rs (q/s) => pq/rs = (q/s)/(s/q) => pq/rs = q^2/s^2. Using this in (1) we get (p^2+q^2)/(r^2+s^2) = q^2/s^2 = pq/rs. Reply

Answer:I think so this will be solution.

Step-by-step explanation:Correct option is

B

qr=p

2

+

a

c

As a(p+q)

2

+2bpq+c=0 and a(p+r)

2

+2bpr+c=0

Then q,r are roots of

a(p+x)

2

+2bpx+c=0

⇒ap

2

+ax

2

+2pax+2bpx+c=0

⇒ax

2

+(2pa+2pb)x+c+ap

2

=0

Hence, product of roots is

qr=

a

c+ap

2

⇒qr=p

2

+

a

c

p:q = r:s => p/q = r/s . Squaring both sides

p^2/q^2 = r^2/s^2

=> (p^2+q^2)/q^2 = (r^2+s^2)/s^2

=> (p^2+q^2)/(r^2+s^2) = q^2/s^2 ……(1)

p/q = r/s. Multiplying both sides with qs

=> pqs/q = rqs/s => pq(s/q)= rs (q/s)

=> pq/rs = (q/s)/(s/q)

=> pq/rs = q^2/s^2. Using this in (1) we get

(p^2+q^2)/(r^2+s^2) = q^2/s^2 = pq/rs.